IMPLEMENTASI KEPALA SEKOLAH DALAM PENGEMBANGAN KOMPETENSI PROFESIONAL GURU UNTUK MENINGKATKAN MUTU PENDIDIKAN DI MA HASANUDDIN TELUKBETUNG BANDAR LAMPUNG - Meitha Pravita Sari; Afif Ansori; Rita Linda (UNISAN JURNAL, 2023)
Teachers are the key to the success of an educational institution. Good bad behavior or teaching procedures for teachers will greatly affect the image of educational institutions. In the modern era of globalization, the progress of science and technology is increasing and experiencing very fast exchanges. Professionalism in this field is needed, especially teacher professionalism. In realizing the visit to MA Hasanuddin Telukbetung Bandar Lampung, of course there is a role for professional teacher resources, as supporters who are able to provide a complete and comprehensive education that is contained and can improve the quality of education at MA Hasanuddin Telukbetung Bandar Lampung. This study aims to examine and explore the development of teacher professional strategies at MA Hasanuddin Telukbetung Kota Bandar Lampung with a focus on discussion on: 1) Principal leadership strategies, 2) faced in developing professional competence, 3) teacher professional competency development models suggested to front. This study uses a descriptive approach. Data was collected by using interview, observation, and documentation techniques. Data analysis techniques include data reduction, data presentation and conclusion drawing. The validity of the data is checked by adding the participation of researchers; triangulation techniques using various sources, theories, and methods; and observations. Research informants are principals, waka curriculum and teachers. The results of the study show that: (1) the principal's leadership strategy in developing professional teacher competence to improve the quality of education, the first is a formal strategy, namely the teacher is assigned by the institution to attend education & training, the second is a non-formal strategy, namely the teacher's own desire and effort to train and develop related to his job or position. (2) There are several obstacles faced in developing professional teacher competence, namely the lack or lack of IT mastery in schools and limited time, the lack of teacher creativity in the learning process in the classroom and the lack of a collection of books or school facilities, as well as the lack of scientific work produced by teachers. teacher. (3) a model that can be used to improve teacher professionalism in running the program, namely through in-service training or in-service training programs.